MRI findings and surgical treatment of a carpal synovial cyst in a dog. Issue 2 (21st April 2020) - Tzounos, Caitlin; Taeymans, Olivier; Quinn, Rob; Haimel, Georg
Abstract : A male neutered pug aged 3 years and 3 months presented with a 4‐month history of persistent left thoracic limb lameness, which was associated with a firm swelling on the palmerolateral aspect of the carpus. MRI confirmed a fluid‐filled structure, which appeared to be associated with the joint space. The structure was surgically excised. Histopathology confirmed a true synovial cyst. Follow‐up by telephone and email with the owner 18 months after surgery confirmed the patient was clinically well, with complete resolution of the lameness and no recurrence of swelling. This report discusses the MRI characteristics and successful treatment of a carpal synovial cyst causing lameness in the absence of osteoarthritis. There was long‐term resolution of clinical signs with surgical excision of the cyst.